Healthy and Sustainable Food Shopping: A Survey of Intentions and Motivations - Blanke, Julia; Billieux, Joël; Vögele, Claus (Frontiers in Nutrition, 2022)
Objectives: To determine the relationship between sustainable and healthy food shopping behaviour comparing general motivation with the immediate intention to act. Method: We conducted an online survey of 144 staff at the Cork Institute of Technology, Ireland, using a questionnaire based on the Theory of Planned Behaviour and the Self-Determination Theory to compute the Behavioural Intention score and the Relative Autonomy Index in relation to healthy and sustainable grocery shopping. Results: The intention to shop healthy food was higher (p<0.001, Cohen’s d=0.56) than the intention to shop in a sustainable way. A significant intention-action gap was observed for both healthy (p<0.001, Cohen’s d=0.97) and sustainable grocery shopping (p<0.001, Cohen’s d=1.78). While there was a significant correlation (p<0.001) between the longer-term motivations to act in a healthy and sustainable way, this association was not significant (p=0.16) for the more short-term Behavioural Intention scores. Conclusion and implications: Health was identified as a more important driver for dietary behaviour compared to sustainability. While longer-term motivation shows a stronger correlation between healthy and sustainable grocery shopping, short-term intentions do not follow this pattern as strongly. A significant intention-action gap exists for both, which is stronger for sustainability than for health.